Indian Department Headquarters Records, 1844–1861: A Case Study in Recordkeeping and Archival Custody - Russell, Bill (Archivaria, 2013)
This study describes the records management system and practices of the Indian Department headquarters, 1844–1861, the period during which the civil secretary to the governor general served as superintendent general of Indian Affairs (SGIA). In the history of Indian Department recordkeeping, the period was a preface to transition. The SGIA office was small; its practices reflected a laissez-faire approach to business; its records world was one of dockets and letter books, registers and abstracts, document forms that are unfamiliar to much of the researching public today. Momentous changes were to come in the last quarter of the nineteenth century, when a paper explosion occasioned by geographical expansion and the demands of assimilation policies forced the agency to address the inadequacies of a records management system designed for a less complex bureaucracy. The article then sketches the route by which the records of the SGIA office travelled from contemporary use through semi-active departmental storage to archival custody and to their present state of arrangement and description at Library and Archives Canada. RÉSUMÉ Cette étude décrit les systèmes de gestion de documents et les pratiques du bureau du ministère indien, 1844-1861, période durant laquelle le secrétaire du gouverneur général servait comme surintendant en chef des affaires indiennes. Dans l’histoire de la gestion des documents du ministère indien, cette période a précédé une transition. Le bureau du surintendant en chef du ministère indien était petit et ses pratiques reflétaient une approche laissez-faire; les documents se trouvaient dans des dossiers (« dockets »), des livres de copies de lettres, des registres et des sommaires, des formes de documents qui sont inconnus de la plupart des chercheurs d’aujourd’hui. D’énormes changements devaient encore se produire dans le dernier quart du XIXe siècle quand la prolifération du papier, résultant de l’expansion géographique et des besoins des politiques d’assimilation, a obligé l’agence de se pencher sur les lacunes d’un système de gestion de documents conçu pour une bureaucratie beaucoup moins complexe. Cet article dresse le chemin par lequel les documents du bureau du ministère indien ont voyagé à partir de l’entreposage semi-actif du ministère jusqu’à leur versement aux archives et leur état actuel de classement et de description à Bibliothèque et Archives Canada.